1995
DOI: 10.1038/jcbfm.1995.78
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Responses under Controlled and Monitored Physiological Conditions in the Anesthetized Mouse

Abstract: Summary: Control of physiological parameters such as respiration, blood pressure, and arterial blood gases has been difficult in the mouse due to the lack of technology required to monitor these parameters in small animals. Here we report that anesthetized and artificially venti lated mice can be maintained under physiological control for several hours with apparently normal cerebrovascular reactivity to hypercapnia and mechanical vibrissal stim ulation. SV -129 mice were anesthetized with urethane (750 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
52
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 19 publications
13
52
0
Order By: Relevance
“…5, Table 3), similar in amplitude to our previous observations using LDF (Dalkara et al, 1995;Ma et al, 1996b). The CO 2 reactivity index was 1.4 ± 0.3, compared to a previously published value of 1.8 (Dalkara et al, 1995).…”
Section: Hypercapniasupporting
confidence: 90%
“…5, Table 3), similar in amplitude to our previous observations using LDF (Dalkara et al, 1995;Ma et al, 1996b). The CO 2 reactivity index was 1.4 ± 0.3, compared to a previously published value of 1.8 (Dalkara et al, 1995).…”
Section: Hypercapniasupporting
confidence: 90%
“…Data obtained in our laboratory has shown that mice breathing spontaneously during anaesthesia with ketamine/medetomidine had severely disturbed blood parameters (tHb 13.47 0.42 g%, pO 2 107724.7 mmHg, pCO 2 97.0724.7 mmHg and pH 7.0070.05). This was also the case in CD-1 mice breathing spontaneously while under anaesthesia with chloral hydrate and xylazine (Dalkara et al 1995). The observed arterial pO 2 and pCO 2 of the mechanically ventilated mice in this study had values similar to mice that underwent 40 min of open chest operation and were mechanically ventilated (Guo et al 1998).…”
Section: Time (Minutes)supporting
confidence: 75%
“…That this model allows surgicical interventions was confirmed by the lack of the hind leg withdrawal reflex during laparotomy or thoracotomy. This deep level of anesthesia may explain why arterial blood pressure in our model can be lower than blood pressure in anesthetized mice reported by some studies (4,13).…”
Section: Anesthesia Effect On Blood Pressure and Hrmentioning
confidence: 42%
“…Although it is very important, few studies have systematically looked at these aspects for the mouse within one experimental design. In many hemodynamic studies, the anesthetic regimen of choice has been urethane and/or ␣-chloralose, which was recently recommended for the mouse (4,17). However, in our study, the urethane/␣-chloralose combination was inferior in terms of blood pressure and HR when compared with a fentanyl-fluanisone-midazolam (FFM) regimen (15).…”
mentioning
confidence: 67%